Equisetum sylvaticum base reduces atherosclerosis risk factors in rats fed a high-fat diet - Cheng-He Lin; Hua-Li Xu; Wei-Lun Sun; Feng Li; Guang-Zhu Lin (Bangladesh Pharmacological Society, 2014)
We identify an Equisetum sylvaticum alkaloid (ESA) derived from E. hyemale, which has robust antihyperlipidemic effects in rats fed a high-fat diet. ESA was isolated from E. hyemale and identified by IR, 13C NMR and 1H NMR. Rats were induced to hyperlipidemia and subjected to ESA treatment. In hyperlipidemic model, fed with a high-fat diet, the blood levels of TC, TG and LDL-C were increased. The administration of ESA (20 or 40 mg/kg) to those rats significantly improved the HDL-C level and reduced the levels of TC, TG, LDL-C. The atherosclerosis index and atherosclerosis risk of these rats were significantly reduced by ESA. In addition, the administration of ESA in rats increased the activity of SOD and decreased the level of MDA. These results reveal the antihyperlipidemic and anti-oxidative effects of ESA in vivo.